Anhedonia and Substance Dependence: Clinical Correlates and Treatment Options - Hatzigiakoumis, Daniele Stavros; Martinotti, Giovanni; Di Giannantonio, Massimo; Janiri, Luigi (Frontiers in Psychiatry, 2011)
Anhedonia is a condition in which the capacity of experiencing pleasure is totally or partially lost, and it refers to both a state symptom in various psychiatric disorders and a personality trait. It has a putative neural substrate, consisting in the dopaminergic mesolimbic and mesocortical reward circuit. Anhedonia frequently occurs in mood disorders, as a negative symptom in schizophrenia, and in substance use disorders. In particular, we focus our attention on the relationships occurring between anhedonia and substance use disorders, as highlighted by many studies. Several authors suggested that anhedonia is an important factor involved in relapse as well as in the transition from recreational use to excessive drug intake. In particular, anhedonia has been found to be a frequent feature in alcoholics and addicted patients during acute and chronic withdrawal as well as in cocaine, stimulant and cannabis abusers. Furthermore, in subjects with a substance dependence disorder, there is a significant correlation between anhedonia, craving, intensity of withdrawal symptoms and psychosocial and personality characteristics. Therefore treating anhedonia in detoxified alcohol dependent subjects could be critical in terms of relapse prevention strategies, given its strong relationship with craving. On this purpose many different strategies have been proposed.